The Holodomor of 1932–1933 in Memory Politics during the Russo–Ukrainian War - Latysh, Yurii (Genocidas ir rezistencija, 2024)
In the Ukraine’s politics of memory, the Holodomor of 1932–1933 takes a key place as the genocide of the Ukrainian people, which aimed to prevent the formation of the Ukrainian nation and the separation of Ukraine from the USSR. During the Russo–Ukrainian War, the emphasis of mnemonic politics was shifted from the victimhood of Ukrainians to their resistance, which prevented the Kremlin from implementing its plans. Ukrainian historians criticised the unreasonable overestimation of the number of Holodomor victims to 10.5 million people, contrary to studies by demographers who estimated the direct losses from famine-induced supermortality in 1932–1934 at 3.94 million, and 4.5 million together with children not born in those years. Instead of the crimes of the communist totalitarian regime, Russian guilt became the key concept in the description of the Holodomor. Putin’s policy of weaponising food, tragedies of Bucha, Irpin and Mariupol are considered as a continuation of the genocidal imperial policy of Russia/the USSR. The Holodomor memory politics is aimed at breaking any ties with Russia.